2011
DOI: 10.1128/cvi.05037-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemotherapy on Whole-Blood Cytokine Responses to Mycobacterium tuberculosis Antigens in a Small Cohort of Patients with Pulmonary Tuberculosis

Abstract: The development of genomic and proteomic tools has enabled studies that begin to characterize the molecular targets of an effective host immune response to Mycobacterium tuberculosis, including understanding the specific immune responses associated with tuberculosis (TB) disease progression, disease resolution, and the development of latency. One application of such tools is the development of diagnostic reagents and assays useful as a test of cure. Such a test could be of considerable importance for the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…In addition to difference in laboratory methods, there were disparities between studies in patient selection, and timing of sampling. For TB-antigen stimulated TNF-a, for example, four of the eight studies included less than 20 patients with active TB [28,31,38,44]. The study design also varied.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition to difference in laboratory methods, there were disparities between studies in patient selection, and timing of sampling. For TB-antigen stimulated TNF-a, for example, four of the eight studies included less than 20 patients with active TB [28,31,38,44]. The study design also varied.…”
Section: Discussionmentioning
confidence: 95%
“…All five studies found an increase in polyfunctional T cells producing IL-2 and other cytokines at the end of treatment [31,36,38,40,44]. One small pilot study (including only 6 participants), using xMAP Luminex to determine cytokine levels, found no change in IL-2 responses with treatment [28].…”
Section: Il-2 Responsesmentioning
confidence: 93%
See 3 more Smart Citations